Exploring Plant Growth-Promoting Traits of Endophytic Fungi Isolated from Ligusticum chuanxiong Hort and Their Interaction in Plant Growth and Development - Qing Wang; Xinyu Zhang; Qiqi Xie; Jiwen Tao; Yujie Jia; Yirong Xiao; Zizhong Tang; Qingfeng Li; Ming Yuan; Tongliang Bu (Journal of Fungi)
Endophytic fungi inhabit various plant tissues and organs without inducing evident disease symptoms. They can contribute positively to the growth of plants, bolster plants resilience to environmental and biological stresses, and facilitate the accumulation of secondary metabolites. These microbial resources possess significant developmental and utilization value in various applications. Hence, this study focused on exploring the plant growth-promoting (PGP) traits of 14 endophytic fungi from Ligusticum chuanxiong Hort (CX) and elucidating the effects and mechanisms that facilitate plant growth. According to PGP activity evaluation, the majority of strains demonstrated the capacity to produce IAA (78.57%), siderophores (50.00%), ammonia (35.71%), potassium solubilization (21.43%), nitrogen fixation (57.14%), and phosphate solubilization (42.86%). Further investigations indicated that the levels of IAA ranged from 13.05 to 301.43 μg/mL, whereas the soluble phosphorus levels ranged from 47.32 to 125.95 μg/mL. In cocultivation assays, it was indicated that Fusarium sp. YMY5, Colletotrichum sp. YMY6, Alternaria sp. ZZ10 and Fusarium sp. ZZ13 had a certain promoting effect on lateral root number and fresh weight of tobacco. Furthermore, ZZ10 and ZZ13 significantly enhanced the germination potential, germination index, and vigor index of tobacco seeds. The subsequent potted trials demonstrated that the four endophytic fungi exhibited an enhancement to growth parameters of tobacco to a certain extent. ZZ10 and ZZ13 treatment had the best promotion effect. Inoculation with YMY5 increased the chlorophyll a and total chlorophyll content. ZZ10 and ZZ13 treatment remarkably increased the net photosynthetic rate, soluble sugars and soluble protein content, catalase and peroxidase activities, and lowered malondialdehyde content in tobacco leaves. In addition, YMY5 remarkably elevated superoxide dismutase activities. ZZ13 upregulated the expression of growth-related gene. Among them, ZZ13 had a better growth-promoting effect. In conclusion, these endophytic fungi possessing multi-trait characteristics and the capacity to enhance plant growth exhibit promising potential as biofertilizers or plant growth regulators.